Heat shock protein family B member 1 facilitates ezrin activation to control cell migration in esophageal squamous cell carcinoma. (July 2019) - Xie, Ying-Hua; Li, Li-Yan; He, Jian-Zhong; Xu, Xiu-E; Liao, Lian-Di; Zhang, Qiang; Xie, Jian-Jun; Xu, Li-Yan; Li, En-Min
Graphical abstract: Highlights: Identify a novel interaction between ezrin and HSPB1 in ESCC cells. HSPB1 interacts with inactive ezrin and binds to the α-helical coiled coil region of ezrin. Knockdown of HSPB1 resulted to the decline of phosphorylation at ezrin Thr567, markedly suppressing migration of ESCC cells. Low HSPB1 expression was associated with favorable overall survival and disease-free survival of ESCC patients. Abstract: Ezrin plays an important role in the development and progression of human esophageal squamous cell carcinoma (ESCC), providing a link between the cortical actin cytoskeleton and the plasma membrane to govern membrane structure and protrusions. However, the mechanism by which ezrin is activated still remains unknown in ESCC. Here, we identify a novel interaction between ezrin and heat shock protein family B (small) member 1 (HSPB1) in ESCC cells by mass spectroscopy and co-immunoprecipitation. HSPB1 only interacts with inactive ezrin and binds to the α-helical coiled coil region of ezrin. Knockdown of HSPB1 resulted to the decline of phosphorylation at ezrin Thr567, markedly suppressing the ability of ezrin to bind to the actin cytoskeleton and migration of ESCC cells. Furthermore, neither the constitutively active phosphomimetic ezrin T567D, nor inactivated ezrin T567A could restore cell migration following HSPB1 knockdown. Low HSPB1 expression was associated with favorable overall survival of ESCC patients. Taken together, HSPB1, as an important partner, participates in the activation of ezrin and merits further evaluation as a novel therapeutic target against human ESCC.